Plant Phenology Dynamics and Pollination Networks in Summits of the High Tropical Andes: A Baseline for Monitoring Climate Change Impacts - Pelayo, Roxibell C.; Llambí, Luis D.; Gámez, Luis E.; Barrios, Yeni C.; Ramirez, Lirey A.; Torres, J. Eloy; Cuesta, Francisco (Frontiers in Ecology and Evolution, 2021)
Analysing plant phenology and plant-animal interaction networks can provide sensitive mechanistic indicators to understand the response of alpine plant communities to climate change. However, monitoring data to analyse these processes is scarce in alpine ecosystems, particularly in the highland tropics. The Andean páramos constitute the coldest biodiversity hotspot on Earth, and their species and ecosystems are among the most exposed and vulnerable to the effects of climate change. Here, we analyse for the first-time baseline data for monitoring plant phenological dynamics and plant-pollinator networks along an elevation gradient between 4200 and 4600 m asl in three mountain summits of the Venezuelan Andes, which are part of the GLORIA monitoring network. We estimated the presence and density of plants with flowers in all the summits and in permanent plots, every month for one year. Additionally, we identified pollinators. We calculated a phenological overlap index between species. We summarized the plant-pollinator interactions as a bipartite matrix and represented a quantitative plant-pollinator network, calculating structural properties (grade, connectance, nestedness and specialization). We also evaluated whether the overall network structure was influenced by differences in sampling effort, changes in species composition between summits and phenology of the plant species. Finally, we characterized the pollination syndrome of all species. Flowering showed a marked seasonality, with a peak towards the end of the wet season. The overall phenological overlap index was low (0.32), suggesting little synchrony in flowering among species. Species richness of both plants and pollinators decreased along the elevation gradient. Flies, bumblebees and hummingbirds were the most frequent pollinators in the network, while entomophily and anemophily were the prevailing pollination syndromes. The interaction network in all summits showed high connectance values, significant specialisation (H2) and low nestedness. We did not find a significant effect of sampling effort, summit plant species composition or plant phenology on network structure. Our results indicate that these high tropical alpine plant communities and their plant-pollination networks could be particularly vulnerable to the loss of species in climate change scenarios, given their low species richness and functional redundancy coupled with a high degree of specialization and endemism.